Malawi: Cost effective options for inclusive and sustainable development - Aragie, Emerta A.; Kankwamba, Henry; Pauw, Karl; Thurlow, James; Jones, Eleanor (International Food Policy Research Institute, 2025)
In this policy brief, we present findings of a systematic evaluation and ranking of investment options for Malawi’s agrifood system based on their cost-effectiveness in achieving multiple development outcomes, including agrifood gross domestic product (GDP) growth, agrifood job creation, poverty reduction, declining undernourishment, and lowering diet deprivation. Additionally, the study assesses their environmental footprint, focusing on water consumption, land use, and emissions. Investments in small and medium enterprise (SME) processors, seed systems, and farmers credit are shown to be the most cost-effective at driving improvements in social outcomes, like poverty and undernourishment. They are also highly ranked in terms of expanding agrifood GDP and employment. Investments in extension and advisory services for livestock, SME traders, and seed subsidy also rank high. However, many cost-effective investments have relatively high environmental footprints, which highlights potential tradeoffs. The study further reveals shifts in the cost-effectiveness ranking of in vestment options overtime and when extreme production shocks occur.